Design and Synthesis of New Circularly Polarized Thermally Activated Delayed Fluorescence Emitters - Feuillastre, Sophie (J Am Chem Soc, 2016)
This work describes the first thermally activated delayed fluorescence material enabling circularly polarized light emission through chiral perturbation. These new molecular architectures obtained through a scalable one-pot sequential synthetic procedure at room temperature (83% yield) display high quantum yield (up to 74%) and circularly polarized luminescence with an absolute luminescence dissymmetry factor, |g(lum)|, of 1.3 × 10(−3). These chiral molecules have been used as an emissive dopant in an organic light emitting diode exhibiting external quantum efficiency as high as 9.1%.